2005
DOI: 10.1519/14253.1
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Acceleration, Maximum Speed, and Agility in Professional Soccer Players

Abstract: High-speed actions are known to impact soccer performance and can be categorized into actions requiring maximal speed, acceleration, or agility. Contradictory findings have been reported as to the extent of the relationship between the different speed components. This study comprised 106 professional soccer players who were assessed for 10-m sprint (acceleration), flying 20-m sprint (maximum speed), and zigzag agility performance. Although performances in the three tests were all significantly correlated (p < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
338
5
48

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(413 citation statements)
references
References 8 publications
22
338
5
48
Order By: Relevance
“…Despite the evolutionary conservation of α-actinin-3, a significant proportion of healthy individuals (for example, ∼18% of Caucasians of European ancestry) are totally deficient in this protein as they are homozygous for a premature stop codon polymorphism (577X) in ACTN3 14. Although this genetic variant is not associated with a known disease phenotype, it is believed to preclude top-level athletic performance in power and sprint activities, as opposed to the 577R polymorphism 16 17. However, no data are available on elite soccer players.…”
mentioning
confidence: 99%
“…Despite the evolutionary conservation of α-actinin-3, a significant proportion of healthy individuals (for example, ∼18% of Caucasians of European ancestry) are totally deficient in this protein as they are homozygous for a premature stop codon polymorphism (577X) in ACTN3 14. Although this genetic variant is not associated with a known disease phenotype, it is believed to preclude top-level athletic performance in power and sprint activities, as opposed to the 577R polymorphism 16 17. However, no data are available on elite soccer players.…”
mentioning
confidence: 99%
“…Some authors have speculated about the relationship between dynamic balance and agility. For instance, balance training induced a positive transference to agility performance (Little & Williams, 2005). Additionally, sports requiring agility skills have demonstrated superior static unipedal and dynamic balance ability compared with control participants (Bressel, Yonker, Kras, & Heath, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, balance is considered an agility subcomponent (Ruiz et al, 2009) and agility is de ned as a body movement with velocity or direction changes in response to a stimulus (Sheppard & Young, 2006). Studies showed an agility/balance relationship through agility improvements after a balance training intervention (Little & Williams, 2005). Nevertheless, scienti c literature that provides direct agility/balance relationship is scarce, especially in children.…”
Section: Introductionmentioning
confidence: 99%
“…A study has revealed a high correlation with the maximal speed and acceleration (Mendez-Villanueva et al, 2011), while the same relationship is not observed between agility and linear sprints. (Little & Williams, 2005;Sheppard & Young, n.d.;Warren B Young et al, 2001) The more interesting result of another study is with 36 male participants. In this study one group made agility training while other made linear sprint training for 6 weeks.…”
Section: Extended English Abstractmentioning
confidence: 89%
“…(Little & Williams, 2005;Sheppard & Young, 2006;Warren B Young, Mcdowell, & Scarlett, 2001) Ayrı bir çalışmada 15 futbolcu ile yapılan toplu ve topsuz zigzag testleri ile 10m, 20m testleri arasında pozitif ilişkiye rastlanırken, (Köklü, Alemdaroğlu, Özkan, Koz, & Ersöz, 2015) yine futbolcularda yapılan araştırmada 20m sprint ve 20m çeviklik testleri arasında bir ilişki çıkmamıştır. (D. Buttifant, K. Graham, 2002) Fakat genel olarak ortaya koyulan bulgular sürat ve çevikliğin farklı motorik özellikler olduğunu, aralarındaki ilişkinin düşük olduğunu göstermektedir.…”
Section: Discussionunclassified